Long-term effects of the consumption of Stevia rebaudiana (Magnoliopsida, Asteraceae) on fertility mice’s - Gil, Juan C. (2008)
The objective of this work was to determine the long-term effects of consuming aqueous extracts of Stevia rebaudiana (Bertoni) leaves on the number of offspring, microscopic morphology of genitalia, and levels of testosterone and estrogens in albino mice. We studied four groups of mice, each consisting of 6 males and 6 females. One group was the control (C) and received food and plain water. Three groups received treatment of food and water with extract of S. rebaudiana at concentrations of (g/Kg) 3,75g (I), 7,5 (II) and 15 (III) for a period of 120 days. The offspring were counted and the histology of genitalia among the groups was compared. Serum levels of total testosterone and estrogens were measured by immunoassay and sexual behaviour was observed. Levels of total testosterone (ng/mL) were significantly different between groups (C= 1,02±0,03; I=1,12±0,01; II= 1,16±0,02; III= 1,21±0,01). Likewise were also significantly different the levels of total estrogens (pg/mL) (C= 20,77±7,22; I= 30,58±2,07; II= 33,08±3,45; III= 43,58±10,3). But no significant differences were observed between the weights (g) of the uterus, tubes and ovaries in group (C= 0,065±0,005; I= 0,058±0,007, II= 0,058±0,007; III= 0,056±0,005). The weight (g) of the testicles showed significant differences only with the treatment III (C= 0,153±0,005; I= 0,155±0,005, II= 0,145±0,005; III= 0,110±0,008). Histological differences in the genital organs between control group and the treatment groups were not detected. Libido in male mice treated with SrB was increased. The weight of the offspring (g) was higher and statistically different in groups II and III (C= 7,53±0,26; I= 7,86±0,47; II= 9,37±0,66; III= 9,35±0,45). The number of offspring was lower and significantly different for treatments II and III (C= 10,83±0,75; I= 11,83±1,17; II= 8,66±0,52; III= 9,17±0,98). We conclude that consumption of SrB does not affect fertility in mice. However, SrB consumption is associated with markedly diminished weight of the testicles accompanied by increased testosterone and estrogens levels.